Application of Mendelian randomization analysis to explore causal associations of aspirin use with bone mineral density and risk of fracture - Qi-Pei Liu (Hereditas)
Abstract Objective Previous observational studies on the association between aspirin use, bone mineral density (BMD), and fracture risk have yielded controversial results. This study explored the causal relationship between aspirin use, BMD, and fracture risk using Mendelian randomization (MR). Methods Summary data for aspirin use and BMD of five different body parts (femoral neck, lumbar spine, forearm, heel, and ultra distal forearm) and fractures were obtained from the integrative epidemiology unit open genome-wide association studies database for bidirectional MR analysis. An appropriate model was chosen based on Cochran's Q test, with inverse variance-weighted as the primary method for MR analysis, supplemented by the weighted-median and MR-Egger methods. MR-Egger and MR-PRESSO were used to test for horizontal pleiotropy and exclude significant outliers that could bias the results. Various sensitivity analyses, including leave-one-out analysis, were conducted to ensure the robustness of the findings. Results Aspirin use significantly increased lumbar spine BMD (odds ratio [OR] = 4.660; 95% confidence interval [CI]: 1.365–15.906; P = 0.014). No significant causal association was found between aspirin use and fracture risk (beta = 59.951; 95% CI: -265.189–385.091; P = 0.718). No significant reverse causality was observed. Conclusion This study indicates that aspirin use does not significantly affect fracture risk but has a significant protective effect on lumbar spine BMD, revealing a potential benefit of aspirin against osteoporosis.